The Association Between the Number of Prehospital Providers On-Scene and Out-of-Hospital Cardiac Arrest Outcomes. (2nd November 2022) - Lupton, Joshua R.; Neth, Mathew R.; Sahni, Ritu; Wittwer, Lynn; Le, Nancy; Jui, Jonathan; Newgard, Craig D.; Daya, Mohamud R.
Abstract: Objective: The ideal number of emergency medical services (EMS) providers needed on-scene during an out-of-hospital cardiac arrest (OHCA) resuscitation is unknown. Our objective was to evaluate the association between the number of providers on-scene and OHCA outcomes. Methods: This was a secondary analysis of adults ( ≥ 18 years old) with non-traumatic OHCA from a 10-site North American prospective cardiac arrest registry (Resuscitation Outcomes Consortium) including a 2005–2011 cohort and a 2011–2015 cohort. The primary outcome was survival to hospital discharge. We calculated the median number of EMS providers on-scene during the first 10 minutes of the resuscitation and used multivariable logistic regression adjusting for age, sex, witness status, bystander CPR, arrest location, initial rhythm, and dispatch to EMS arrival time. Results: There were 30, 613 and 41, 946 patients with necessary variables in the 2005–2011 and 2011–2015 cohorts, respectively. Survival to hospital discharge (95% CI) was higher with 9 or more providers on-scene (17.2% [15.8–18.5] and 14.0% [12.6–15.4]) compared to 7–8 (14.1% [13.4–14.8] and 10.5% [9.9–11.1]), 5–6 (10.0% [9.5–10.5] and 8.5% [8.1–8.9]), 3–4 (10.5% [9.3–11.6] and 9.3% [8.5–10.1]), and 1–2 (8.6% [7.2–10.0] and 8.0% [7.1–9.0]) providers for the 2005–2011 and 2011–2015 cohorts, respectively. In multivariable logistic regressions, compared to 5–6 providers, there were no significant differences in survival to hospital discharge for 1–2 or 3–4 providers, while having 7–8 (adjusted odds ratios (aORs) 1.53 [1.39–1.67] and 1.31 [1.20–1.44]) and 9 or more (aORs 1.76 [1.56–1.98] and 1.63 [1.41–1.89]) providers were associated with improved survival in both the 2005–2011 and 2011–2015 cohorts, respectively. Conclusions: The presence of seven or more prehospital providers on-scene was associated with significantly greater adjusted odds of survival to hospital discharge after OHCA compared to fewer on-scene providers.